Complications Following Umbilical Vein Catheterization in Preterm Neonates - Single-Center - Marija Djermanovic; Slobodan Spasojevic; Tanja Radovanovic (Mashhad University of Medical Sciences, 2024)
Background: Despite their widespread use, umbilical venous catheters (UVCs) are associated with various complications. Methods: This single-center retrospective cohort study examined UVC-related complications in preterm neonates within a tertiary Neonatal Intensive Care Unit (NICU) from January 2020 to December 2022. The study aimed to analyze these complications in relation to UVC positioning. Results: Over the course of three years, 146 preterm neonates underwent UVC insertion. The cohort's mean gestational age was 29.2 ± 3 weeks, with a median birth weight of 1110 g (817-1482 g). The median UVC placement duration was 8 days (6-10), totalling 1220 catheter days. Overall, 37% of the UVC placements were categorized as optimal, 35.6% as low-lying, 20.5% as high-lying, and 6.8% were categorized as malpositioned. The UVC-related complications occurred in 62 neonates (42.5%), with central line-associated bloodstream infection (CLABSI) in 8.2%, portal vein thrombosis (PVT) in 2.7%, pericardial effusion in 0.7%, and necrotizing enterocolitis (NEC) in 2.7% of neonates. The incidence of UVC-related complications was lowest with high-lying positions (23.3%), followed by optimal positioning (31.5%), low-lying (63.5%), and the highest in malpositioned UVCs (70%). UVC placement exceeding 8 days were significantly associated with increased complications. Conclusion: The study highlights an elevated rate of complications associated with umbilical vein catheterization emphasizing the need for judicious use, especially in preterm neonates.